How does it really feel to be in my shoes?: patients' experiences of compassion within nursing care and their perceptions of developing compassionate nurses - Bramley, Louise; Matiti, Milika (Wiley, 2014)
Aims and objectives To understand how patients experience compassion within nursing care and explore their perceptions of developing compassionate nurses.